2023
DOI: 10.3390/ijerph20043674
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Rural and Urban Practices in the Response to the COVID-19 Pandemic: Outcomes from the PRICOV-19 Study in 38 Countries

Abstract: This paper explores the differences between rural and urban practices in the response to the COVID-19 pandemic, emphasizing aspects such as management of patient flow, infection prevention and control, information processing, communication and collaboration. Using a cross-sectional design, data were collected through the online PRICOV-19 questionnaire sent to general practices in 38 countries. Rural practices in our sample were smaller than urban-based practices. They reported an above-average number of old an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
2
1
Order By: Relevance
“…An important finding in our analysis is that what significantly protected Austrian GPs from experiencing distress was working in a rural area (Table 3). This was in contrast to an international study by Petrazzuoli et al [28], who found that rural practices tend to be smaller and smaller practices tend to be associated with higher distress [29]. However, in Austria, rural practices tend to be larger than those in urban areas because this compensates for lower GP density.…”
Section: Discussioncontrasting
confidence: 90%
“…An important finding in our analysis is that what significantly protected Austrian GPs from experiencing distress was working in a rural area (Table 3). This was in contrast to an international study by Petrazzuoli et al [28], who found that rural practices tend to be smaller and smaller practices tend to be associated with higher distress [29]. However, in Austria, rural practices tend to be larger than those in urban areas because this compensates for lower GP density.…”
Section: Discussioncontrasting
confidence: 90%
“…The PRICOV-19 results show that GP practices were highly adaptive in their organisation to deliver safe care for COVID-19 and non-COVID patients. New measures were implemented rapidly, including new patient flow management, triage protocols, infection prevention measures, and communications, such as remote consultations [ 2 , 3 ]. Safety measures already in place before the pandemic, such as adequate time for reviewing guidelines, remained primarly in place.…”
Section: Recommendationsmentioning
confidence: 99%
“…As far as theThe differences between rural and urban GP practices during the COVID-19 pandemic are concerned, they were proveddemonstrated in the general conditions of providing care, as shown in an international comparison [18]. The scopebreadth of the available data allowedwe had access to enabled us to quantify these potential differences inacross various activities to understand better , improving our understanding of how GP practices operatedfunctioned during the pandemic.…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%